A new species of Palaeopoecilostola Meunier, 1899 (Diptera: Limoniidae) from the Eocene Baltic amber - Kania, Iwona; Krzemiński, Wiesław (Zootaxa, 2012)
A new species of the genus Palaeopoecilostola Meunier, 1899 (Diptera: Limoniidae) from the Baltic amber (Upper Eocene) is described. The cladistic analysis of the species included in this genus is provided. The distributional pattern of the Palaeopoecilostola species is discussed. Palaeopoecilostola as numerous and remarkable representative of Limoniidae, can be treated as the marker genus of the Baltic amber in broad sense (including Bitterfeld and Ukrainian ambers). Anepsiomyia atterraneus Nazarov, 1994 is resurrected from synonymy with Palaepoecilostola speciosa Meunier, 1906. Ryta berestiana Nazarov, 1994 appears a junior synonym of Palaepoecilostola speciosa Meunier, 1906.